2021
DOI: 10.1177/03000605211050791
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer characteristics in patients with spontaneous intracranial hypotension: a retrospective case series

Abstract: Objective To evaluate changes in retinal nerve fiber layer (RNFL) and macular thicknesses, included ganglion cell-inner plexiform layer (GCIPL) thickness, in patients with spontaneous intracranial hypotension (SIH). Methods This was a retrospective, nonrandom, observational case series study. Comprehensive ophthalmic examinations and systemic examinations were performed. Spectral domain optical coherence tomography angiography scanning was used to measure peripapillary RNFL thickness and macular volume. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This study concluded that retinal nerve fiber layer and ganglion cell–inner plexiform layer thickness was thinner in patients with intracranial hypotension versus a healthy control 13 . Patients with visual field defects also had thinner ganglion cell–inner plexiform layer thickness, suggesting that changes to the ganglion cell layer may play a role in visual field loss 13 . Further research needs to be conducted to investigate the pathogenesis of how low intracranial pressure impacts retinal structures.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This study concluded that retinal nerve fiber layer and ganglion cell–inner plexiform layer thickness was thinner in patients with intracranial hypotension versus a healthy control 13 . Patients with visual field defects also had thinner ganglion cell–inner plexiform layer thickness, suggesting that changes to the ganglion cell layer may play a role in visual field loss 13 . Further research needs to be conducted to investigate the pathogenesis of how low intracranial pressure impacts retinal structures.…”
Section: Discussionmentioning
confidence: 90%
“…Unlike intracranial hypertension, there is no visual field pattern characteristic of intracranial hypotension. Horton and Fishman 4 discussed two cases of blurry vision with visual obscurations and noted binasal visual field defects in these patients 13 . Groth et al 14 discussed a case of decreased bilateral visual acuity and noted temporal quadrant constriction on visual field testing 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations